AB0121 A novel pharmacoproteomic study confirms the synergistic chondroprotective effect of chondrotin sulfate and glucosamine hydrochloride. (23rd January 2014) - Calamia, V.; Mateos, J.; Fernández-Puente, P.; Lourido, L.; Montell, E.; Vergés, J.; Ruiz-Romero, C.; Blanco, F.J.
Abstract : Background: Recent works by our group provide evidences for the usefulness of proteomics techniques for pharmacological analyses in the rheumatology field, with the aim to identify efficacy markers for monitoring different OA treatments [1, 2] . Objectives: To assess the synergistic chondroprotective effect of chondroitin sulfate (CS) and glucosamine hydrochloride (GH) in modifying cartilage extracellular matrix metabolism by the analysis of proteins secreted from chondrocytes using the iTRAQ technique. Methods: Cartilages obtained from patients undergoing joint replacement were provided by the Tissue Bank and the Autopsy Service at CHU A Coruña. The study was approved by the local Ethics Committee. Chondrocytes released from osteoarthritic (OA) cartilage by enzymatic digestion were recovered and cultured in basic DMEM supplemented with antibiotics and 10% FBS. When confluence was reached, OA chondrocytes were treated with CS alone and in combination with GH (both at 200μg/mL). 48 hours later, conditioned media were collected and their proteins were concentrated and quantified. Trypsin digestion and labeling with isobaric tags using iTRAQ reagents were performed. Then, peptides from the four differentially labeled conditions (untreated, CS-treated, GH-treated, and CS+GH-treated) were mixed, separated and analyzed by nanoscale reversed-phase liquid chromatography coupled to mass spectrometry (nLC-MALDI-MS/MS). Results: We have carried out the first pharmacoproteomic study based on peptides labeling with 4 isobaric tags (iTRAQ) to study the effect of CS, alone and in combination with GH, on the chondrocytes secretome. Database search (UniprotKB/Swissprot) allowed us the identification of 251 different proteins secreted by OA chondrocytes. Among them, we were able to detect collagen alpha-1(II) chain (COL2A1) which has not been previously identified by MS in cultured chondrocytes. For the biological and functional analyses, we consideredonly those proteins with a probability score higher than 95%, and a ratio ≥1.2 or ≤0.8. Finally, 39 secreted proteins presented statistically significant differences ( p ≤0.05)between untreated and treated samples: 23 were increased and 16 decreased (see Table 1). The majority of proteins modulated by CS alone are related to metabolism and energy production. All of them were decreased by the drug, thus confirming similar results obtained by two-dimensional electrophoresis in our previous work [1] . On the other hand, most of the proteins altered by CS in combination with GH are cartilage ECM components, such as collagens and proteoglycans. Conclusions: Considering only those proteins whose expression is altered by the different treatments, it is clear that the two formulations (simple and combined) do not have the same effect. Our findings confirm the synergistic chondroprotective effect of chondrotin sulfate and glucosamine hydrochloride previously described by our group [1] . Moreover, we have successfully quantified the increase of several ECM components caused by the administration of these compounds. References: Calamia V, Ruiz-Romero C, Rocha B, et al. Arthritis Res Ther. 2010. R138. Calamia V, Fernández-Puente P, Mateos J, et al. Mol Cell Proteomics. 2011 Dec 27. Disclosure of Interest: None Declared